PENGEMBANGAN BUKU DIGITAL CERITA BERGAMBAR BERBENTUK FLIPBOOK DALAM PEMBELAJARAN TEMATIK SISWA KELAS V - Melly Monica; Siti Halidjah; Rio Pranata (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2022)
This study aims to describe the steps of developing a digital picture book in the form of a flipbook that is valid and practical in thematic learning for fifth grade students at 39 Pontianak City Elementary School. This study uses the Research and Development (R&D) method based on the ADDIE model which consists of five development steps, namely Analysis, Design, Development, Implementation and Evaluation. The data sources of this research are design experts, material experts and students validators. The results of the validation of design experts and materials experts obtained an average of 5 "very valid". The results of design and material validation for students by small groups obtained an average of 4.45 "very valid". The results of design and material validation for students by large groups obtained an average of 4.51 "very valid". The results of practicality by small groups obtained an average of 4.54 "very practical". The results of practicality by large groups obtained an average of 4.46 "very practical". Based on the results obtained, it can be concluded that the digital illustrated story book in the form of a flipbook in thematic learning is very practical to use in the learning process.Keywords: Digital book, Flipbook, Thematic